A Tale of Amalgamation of Three Permo-Triassic Collage Systems in Central Asia: Oroclines, Sutures, and Terminal Accretion - Xiao W.; Windley B.; Sun S.; Li J.; Huang B.; Han C.; Yuan C.; Sun M.; Chen H. (My University, 2015)
The Central Asian Orogenic Belt records the accretion and convergence of three collage systems that were ﬁnally rotated into two major oroclines. The Mongolia collage system was a long, N–S-oriented composite ribbon that was rotated to its current orientation when the Mongol-Okhotsk orocline was formed. The components of the Kazakhstan collage system were welded together into a long, single composite arc that was bent to form the Kazakhstan orocline. The cratons of Tarim and North China were united and sutured by the Beishan orogen, which terminated with formation of the Solonker suture in northern China. All components of the three collage systems were generated by the Neoproterozoic and were amalgamated in the Permo-Triassic. The Central Asian Orogenic Belt evolved by multiple convergence and accretion of many orogenic components during multiple phases of amalgamation, followed by two phases of orocline rotation
Keywords: paleogeographic separation; palinspastic reconstructions; subduction complex; Mesozoic::Triassic; Палеозой::Пермская; Paleozoic::Permian; Мезозой::Триасовая